2018
DOI: 10.1111/eci.12930
|View full text |Cite
|
Sign up to set email alerts
|

Elevated high‐sensitive troponin T in negative stress test individuals

Abstract: Among subjects referred for EST as part of an annual health survey, we found no significant association between EST results to hs-cTnT detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Likewise, Magioni et al, found hs-cTnT >6 ng/L to be an independent risk factor for CAD in patients with low risk for CAD (27). In a recent publication, Brzezinski et al explored resting troponin levels in relation to exercise stress test in a large cohort of healthy individuals (28). Although their findings propose an insignificant relation of troponin levels and positive or negative stress test results, this healthy and supposedly asymptomatic population is generally not of concern in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Magioni et al, found hs-cTnT >6 ng/L to be an independent risk factor for CAD in patients with low risk for CAD (27). In a recent publication, Brzezinski et al explored resting troponin levels in relation to exercise stress test in a large cohort of healthy individuals (28). Although their findings propose an insignificant relation of troponin levels and positive or negative stress test results, this healthy and supposedly asymptomatic population is generally not of concern in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A power calculation with an alpha risk of 0.05 and a power of 0.80 was performed. In studies including individuals without suspicion of CAD the prevalence of unknown significant CAD has been reported to be 7% [ 17 ] and the incidence of pathological stress test has been reported to be 8% [ 18 ]. Based on this we estimated the incidence of pathological stress test to approximately 7% in the control group and we assumed a clinically highly relevant incidence of 30% in the case group.…”
Section: Methodsmentioning
confidence: 99%
“…We prospectively enrolled consecutive patients attending a routine annual health survey at the Tel-Aviv Medical Center Inflammation Survey (TAMCIS), a registered databank of the Israeli Ministry of Justice [12][13][14][15][16]. Subjects underwent a physician's interview and examination, blood and urine tests, and an exercise stress test.…”
Section: Study Cohortmentioning
confidence: 99%